Optimization Processing Parameters for Curcuma xanthorriza Oleoresin Yield and its Antioxidant Activity - Taher, Zarani M.; Sarmidi, Mohamad R. (International Journal of Biotechnology for Wellness Industries, 2015)
Processing is a critical aspect of herbal based products, and processing method is known to affect the content, activity and bioavailability of bioactive compounds. Extraction of oleoresin from Curcuma xanthorriza is effected by several processing parameters. Appropriate solvent selection such as polar solvent result in better extraction yield while lower polarity solvent end up with extracts having higher concentration of active compounds. In this study, different processing parameters were carried out including blanching treatment (boiled, steamed) at range of time (24 hours, 48 hours and 72 hours), solvent of extraction (methanol, ethanol and acetone). The curcuminoid content and antioxidant activity were determined in Curcuma xanthorriza oleoresin. The result obtained was proved that ethanol was the most effective solvent. Blanching treatment affects the yield of oleoresin and promotes the release of curcuminoids content.